Digital assets in the eyes of Generation Z: Perceptions, outlooks, concerns - Karol Król; Dariusz Zdonek (Journal of Risk and Financial Management, 2023)
The recent decade saw an explosion of digital assets and digitalisation of financial services. The present contribution poses several research questions incorporated into a survey questionnaire and grouped into two categories: (1) associations with, knowledge of, and familiarity with notions relevant to digital assets and (2) perceptions of digital assets and attitude towards investing in them. Invitations to participate were sent to a group of 570 random representatives of Generation Z with 387 correctly completed questionnaires employed in the study. The research demonstrated that it was not insufficient funds that posed the greatest barrier to the growth in digital assets investments. The respondents justified their concerns about digital assets with poor knowledge of cryptocurrencies and non-fungible tokens (NFTs). The scepticism is fuelled mostly by the nontangible nature of digital assets (approx. 23%). The respondents most commonly (123, approx. 47%) associated NFTs with digital works of art, virtual objects, and NFT graphics. Blockchain most often brought to the minds of the respondents databases, algorithms, data recording, transaction data transfer, data cloud transactions, cryptocurrencies, cryptography, and decentralised financial systems. The research seems to suggest a certain difficulty with representing (characterising) the digital ecosystem and virtual reality. The media narrative emphasises the intangible nature of the digital ecosystem, often depicting it as impalpable and unreal, which does not help with how prospective investors view it. Some recommendations emerge from the research that should be considered when drawing a strategy for presenting digital assets, cryptocurrencies, and NFT markets.
Keywords: 650; Generation Z; cryptocurrencies; digital assets; media narrative; non-fungible token